Analisis Peran Bidan Desa dalam Meningkatkan Kepatuhan Ibu pada Pelaksanaan Sub-PIN Polio UPTD Puskesmas Patek - Diana Lestari; Nia Hairu Novita (Vitamin : Jurnal ilmu Kesehatan Umum, 2026)
Background: The re-emergence of a polio outbreak necessitates a rapid response through the Sub-National Immunization Week (Sub-PIN) Polio program. Village midwives, as frontline community health service providers, play a strategic role in determining the success of this program through their influence on maternal compliance. Objective: This study aimed to analyze the role of village midwives in improving maternal compliance with the implementation of Sub-PIN Polio in the working area of UPTD Puskesmas Patek, Aceh Jaya. Methods: This study employed a descriptive qualitative approach. Data were collected through in-depth interviews, observations, and document review. The informants consisted of village midwives, mothers of toddlers, posyandu cadres, and the head of the public health center, selected using purposive sampling. Data were analyzed using the Miles and Huberman model and validated through triangulation techniques. Results: The findings showed that village midwives effectively performed their roles as educators and motivators, successfully reducing mothers’ anxiety regarding Adverse Events Following Immunization (AEFI) and correcting vaccine-related misinformation through interpersonal communication. As social mobilizers, midwives established cross-sector collaboration with Geuchik (village heads) and religious leaders to mobilize community participation. Furthermore, the implementation of a sweeping strategy (door-to-door outreach) by village midwives became a crucial solution to overcome geographical barriers and mothers’ work-related constraints, thereby significantly increasing compliance. Cultural closeness and community trust were identified as the main supporting factors, while adverse weather conditions and digital misinformation were the primary obstacles. Conclusion: The active and comprehensive role of village midwives is a key determinant in improving maternal compliance and achieving immunization coverage targets during public health emergencies.